Sociodemographic characteristics of violence in university students from Huánuco, Peru. / Características sociodemográficas de la violencia en estudiantes universitarios de Huánuco, Perú. - PORTOCARRERO MERINO, Ewer; BARRIONUEVO TORRES, Clorinda Natividad; ORTIZ-AGUI, María; TARAZONA TUCTO, Juan (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The objective was to determine the acceptance of violence related to sociodemographic characteristics. It was a descriptive and cross-sectional study with 1756 students from the Hermilio Valdizán National University, Huánuco, 2019. A sociodemographic file and attitudes scales on violence against women and in the university environment were applied, with prior consent. The Mann-Whitney and Kruskal-Wallis U test was used for p≤0.05. Acceptance of violence was very low (1.6 [from 1 to 5]). In addition, there were significant differences according to age, sex and other sociodemographic characteristics (p≤0.05). In conclusion, the acceptance of violence differs according to sociodemographic characteristics in university students.RESUMEN El objetivo fue determinar la aceptación de la violencia relacionada a características sociodemográficas. Fue un estudio descriptivo y transversal, con 1756 estudiantes de la Universidad Nacional Hermilio Valdizán, Huánuco, 2019. Se aplicó, previo consentimiento, una ficha sociodemográfica y escalas de actitudes sobre violencia contra la mujer y en el ámbito universitario. Se utilizó la prueba U de Mann-Whitney y Kruskal-Wallis para p≤0,05. La aceptación de la violencia fue muy baja (1,6 [de 1 a 5]). Además, hubo diferencias significativas según edad, sexo y otras características sociodemográficas (p≤0,05). Conclusión, la aceptación de la violencia difiere según características sociodemográficas en estudiantes universitarios.